Effect of Surface Oxides and Intermetallics on Nanostructured Diamond Coating of Nitinol - Catledge, Shane A.; Thomas, Vinoy; Vohra, Yogesh K. (Current Nanoscience, 2006)
Microwave plasma chemical vapor deposition (CVD) was used to grow nanostructured diamond onto mechanically polished superelastic Nitinol (NiTi) alloy. As determined by glancing-angle x-ray diffraction, mechanical polishing of the heavily oxidized as-received samples resulted in removal of nickel, Ni3Ti, and TiO2 surface phases, leaving the NiTi austenite (B2 type, CsCl structure) to be detected. Diamond nucleation and growth was impractically slow on the mechanically polished samples and could only yield continuous films at practical growth rates when they were first exposed to plasma annealing to allow formation of oxide and intermetallic phases (Ni3Ti, NiTi2). The ability of a surface layer (composed of oxides and/or the intermetallic phases) to act as a barrier to carbon diffusion may be responsible for an observed increase in interfacial TiC formation leading to practical diamond growth rates of about 1 m/hour.
Keywords: Diamond